Densities straw and luminosity conditions on seed germination on seed germination of Euhphorbia heterophylla - Marques, Renata Pereira; Martins, Dagoberto; Costa, Saulo Ítalo de Almeida; Vitorino, Hermeson dos Santos (Semina: Ciências Agrárias, 2012)
It was studied the influence of sugarcane straw density and light conditions on the germination of seeds of Euphorbia heterophylla under controlled conditions.The experimental design was completely randomized design with four replications of 50 seeds, and the treatments were arranged in a 6 x 5 factorial, with six amount of sugarcane straw (0, 8, 10, 12, 14 and 16 t ha-1) and 5 types of light (constant light, constant darkness, alternating light and dark, short red and far red). The seeds were germinated in plastic type boxes covered byoverlapping layers of straw and kept in germination. Assessments of germination were daily computing the normal seedlings, when they presented protusion roots visible and calculated the germination speed index (IGS). It was observed that the increase of different densities of straw and different wave lengths provided germination ranged from 83 to 97% and IGS between 9.85 to 15.36. The different densities of straw and wavelength did not suppress the germination of E. heterophylla. Therefore, the species was insensitive to light, so the presence of raw sugarcane system can't be considered a potential tool for controlling this species.